2012
DOI: 10.1186/1479-5876-10-37
|View full text |Cite
|
Sign up to set email alerts
|

Cellular therapies for treating pain associated with spinal cord injury

Abstract: Spinal cord injury leads to immense disability and loss of quality of life in human with no satisfactory clinical cure. Cell-based or cell-related therapies have emerged as promising therapeutic potentials both in regeneration of spinal cord and mitigation of neuropathic pain due to spinal cord injury. This article reviews the various options and their latest developments with an update on their therapeutic potentials and clinical trialing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 168 publications
2
7
0
Order By: Relevance
“…A principal finding in this study was that probiotic or ADMSC treatment notably and comparably preserved the functional integrity of peripheral nerves, i.e., upregulated the hyperalgesia threshold, resulting in augmentation of the analgesia of NP. In this way, our finding reinforced the findings of previous research [ 24 , 48 , 49 ]. Of innovative finding in the present study was that combination treatment with probiotics and ADMSCs could even offer a synergic effect on upregulating the thresholds of TPWL and MPWT (i.e., indicated by the pain threshold that was defined as the point beyond which a stimulus caused pain), suggesting that our findings extended the findings of previous investigations [ 24 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A principal finding in this study was that probiotic or ADMSC treatment notably and comparably preserved the functional integrity of peripheral nerves, i.e., upregulated the hyperalgesia threshold, resulting in augmentation of the analgesia of NP. In this way, our finding reinforced the findings of previous research [ 24 , 48 , 49 ]. Of innovative finding in the present study was that combination treatment with probiotics and ADMSCs could even offer a synergic effect on upregulating the thresholds of TPWL and MPWT (i.e., indicated by the pain threshold that was defined as the point beyond which a stimulus caused pain), suggesting that our findings extended the findings of previous investigations [ 24 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this way, our finding reinforced the findings of previous research [ 24 , 48 , 49 ]. Of innovative finding in the present study was that combination treatment with probiotics and ADMSCs could even offer a synergic effect on upregulating the thresholds of TPWL and MPWT (i.e., indicated by the pain threshold that was defined as the point beyond which a stimulus caused pain), suggesting that our findings extended the findings of previous investigations [ 24 , 48 , 49 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Cell-based therapy has been proposed as a novel approach for treating painful peripheral neuropathy [1,2]. Transplantation of mesenchymal stem cells (MSCs) has been demonstrated to be a potentially therapeutic approach for the alleviation of chronic pain from various etiologies [2][3][4][5][6][7][8]. Prior studies have reported pain relief in rodent chronic pain models using systemic administration of MSCs [4,8], but this delivery approach requires large preparations of transplantable cells, depends on a nebulously defined propensity of MSCs to home in on injured tissue, and leads to MSCs trapping in the lung, liver, resulting in off-site tissue damage [9,10], making targeted delivery preferable.…”
Section: Introductionmentioning
confidence: 99%
“…New advances from preclinical and clinical studies offer potential neuroprotective and therapeutic possibilities 3 , 4 ; however, due to the poor intrinsic regenerative capability of the spinal cord, treatment of SCI is still a significant problem. A major challenge in repairing the injured spinal cord is how to regenerate tissue and encourage regrowth of severed axons with cellular and molecular therapies 5 , 6 , although several growth factors have been applied for the treatment of SCI 6 .…”
Section: Introductionmentioning
confidence: 99%